Modelling Land Use in The Gold Belt Territories of Iron Age Southern Zambezia - Robert T. Nyamushosho; Shadreck Chirikure; Ari Sitas; Eric N. Maṱhoho (Land, 2022)
Throughout the world, the entanglement of humans and landscapes varies from area to area depending on the time scale. In southern Africa, the impact of humanity on the physical environment is largely discussed in the context of modern rural and urban societies, and, usually, most contributions come from human geography, agriculture, and earth sciences. Very limited research is usually extended into the deep past, yet the archaeological record is replete with valuable information that gives a long-time depth of past human land use practices. Consequently, the contribution of the physical environment to the development of complexity over time remains poorly understood in most parts of Iron Age (CE 200–1900) southern Zambezia, particularly in Mberengwa and other gold-belt territories that have often received cursory research attention. What remains obscured is how did inhabitants of these gold-belt territories transform their landscapes in the long and short-term and how did these transformations intersect with their everyday lives? In this study, we combined archaeological, historical, and anthropological data of the Zimbabwe tradition societies that lived in ancient Mberengwa to probe these issues. The preliminary outcome suggests that despite vulnerability to high temperatures, tsetse-flies, and low rainfall, Later Iron Age societies that inhabited this gold belt territory were innovative risk-takers who successfully adapted a mix of land use practices to achieve longevity in settlement and prosperity in agropastoralism, mining, crafting, and much more. This proffers useful lessons on sustainable land use. Hopefully, with modification to suit the present, such solutions may help policy makers and modern societies living in similar environments to combat current global challenges related to environmental change.